2017
DOI: 10.3892/ol.2017.5788
|View full text |Cite
|
Sign up to set email alerts
|

Oct4 induces EMT through LEF1/β-catenin dependent WNT signaling pathway in hepatocellular carcinoma

Abstract: Octamer 4 (Oct4), a member of the Pit-Oct-Unc transcription factor family required to maintain self-renewal and pluripotency of embryonic stem cells, has been previously identified to be associated with tumorigenesis and malignant transformation of numerous types of cancer including hepatocellular carcinoma (HCC). The present data shows that Oct4 enhances cancer stem cell properties and increases invasion ability in the Huh7 cell line. To increase understanding of the role of Oct4 in HCC, the present study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 47 publications
4
32
0
Order By: Relevance
“…The mechanisms underlying differential activation of these factors remain poorly understood. Consistent with the report by Sun et al that Oct4 in HCC regulates LEF1 to activate the LEF1/β‐catenin‐dependent WNT signaling pathway and promote EMT, findings of the present study indicate that reciprocal regulation between LEF1 and Oct4 in HCC plays a crucial role in maintaining self‐renewal properties. Such regulation is based on specific promoter binding and transcriptional activation.…”
Section: Discussionsupporting
confidence: 93%
“…The mechanisms underlying differential activation of these factors remain poorly understood. Consistent with the report by Sun et al that Oct4 in HCC regulates LEF1 to activate the LEF1/β‐catenin‐dependent WNT signaling pathway and promote EMT, findings of the present study indicate that reciprocal regulation between LEF1 and Oct4 in HCC plays a crucial role in maintaining self‐renewal properties. Such regulation is based on specific promoter binding and transcriptional activation.…”
Section: Discussionsupporting
confidence: 93%
“…We observed expression of p‐p38 (activated form of p38) and CSC markers (Oct4, SOX2, Klf4, c‐Myc and CD44) was found to be upregulated in cut margin regions of recurrent HNSCC samples as compared to non‐recurrent HNSCC samples. SOX2, Oct4, Klf4, c‐Myc and CD44 serves as CSC markers that play an essential role to maintain stemness and are associated with increased cell migration, invasion and metastasis . Our results highlighted that higher expression of activated form of p38 and CSC markers in the cut margin of recurrent patients might have contributed to minimal residual disease.…”
Section: Discussionmentioning
confidence: 69%
“…A previous study revealed that in hepatocellular carcinoma, OCT4 activates the LEF1/β‐catenin‐dependent Wnt signaling pathway to induce cancer cell EMT 21. Moreover, Tcf/Lef‐Oct4 composite element can bond to the promoter of Mesp1.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, previous studies have reported the crosstalk between OCT4 and the components of the Wnt/β‐catenin signaling pathway. For example, as one of the components in the Wnt/β‐catenin signaling pathway, LEF1 mediates the effects of OCT4 in hepatocellular carcinoma cells undergoing EMT 21. These findings highlight the potential importance of crosstalk between these two pathways.…”
Section: Introductionmentioning
confidence: 90%